Quandaries and Queries


Who is asking: Parent
Level: All

simplify the expression
(a2+n2)/2n = a2 + (a2-n2)/2n

My daughter asked me how i do this i have no idea Please help




I would first multiply both sides of the equation by 2n. This will eliminate the fractions.

[(a2+n2)/2n] 2n = [a2] 2n + [(a2-n2)/2n] 2n

which simplifies to

(a2+n2) = 2 n a2 + (a2-n2)

Simplifing I get

2n(n - a2) = 0

This results in n = 0 or n = a2

However there is a problem here. n=0 is not a solution to the original equation since the expression of the left side of the original equation would be a2/0.



Go to Math Central